Dynamic Stabilization of Syndesmosis Injuries Reduces Complications and Reoperations as Compared With Screw Fixation: A Meta-analysis of Randomized Controlled Trials. Issue 4 (March 2020) - Grassi, Alberto; Samuelsson, Kristian; D'Hooghe, Pieter; Romagnoli, Matteo; Mosca, Massimiliano; Zaffagnini, Stefano; Amendola, Annunziato
Background: Several devices for obtaining dynamic fixation of the syndesmosis have been introduced in recent years, but their efficacy has been tested in only a few randomized controlled trials (RCTs), without demonstrating any clear benefit over the traditional static fixation with screws. Purpose: To perform a level 1 meta-analysis of RCTs to investigate the complications, subjective outcomes, and functional results after dynamic or static fixation of acute syndesmotic injuries. Study Design: Meta-analysis of RCTs. Methods: A systematic literature search was performed of the Medline/PubMed, Cochrane Central Register of Controlled Trials, and Embase electronic databases, as well asClinicalTrials.gov for unpublished studies. Eligible studies were RCTs comparing dynamic fixation and static fixation of acute syndesmosis injuries. A meta-analysis was performed, while bias and quality of evidence were rated according to the Cochrane Database questionnaire and the Grading of Recommendations Assessment, Development and Evaluation guidelines. Results: Dynamic fixation had a significantly reduced relative risk (RR = 0.55, P = .003) of complications—in particular, the presence of inadequate reduction at the final follow-up (RR = 0.36, P = .0008) and the clinical diagnosis of recurrent diastasis or instability (RR = 0.10, P = .03). The effect was more evident when compared with permanent screws (RR = 0.10, P = .0001). The reoperation rate was similar between the groups (RR = 0.64, P = .07); however, the overall risk was reduced after dynamic fixation as compared with static fixation with permanent screws (RR = 0.24, P = .007). The American Orthopaedic Foot & Ankle Society score was significantly higher among patients treated with dynamic fixation—6.06 points higher ( P = .005) at 3 months, 5.21 points ( P = .03) at 12 months, and 8.60 points ( P < .00001) at 24 months—while the Olerud-Molander score was similar. The visual analog scale for pain score was reduced at 6 months (–0.73 points, P = .003) and 12 months (–0.52 points, P = .005), and ankle range of motion increased by 4.36° ( P = .03) with dynamic fixation. The overall quality of evidence ranged from "moderate" to "very low, " owing to a substantial risk of bias, heterogeneity, indirectness of outcome reporting, and evaluation of a limited number of patients. Conclusion: The dynamic fixation of syndesmotic injuries was able to reduce the number of complications and improve clinical outcomes as compared with static screw fixation—especially malreduction and clinical instability or diastasis—at a follow-up of 2 years. A lower risk of reoperation was found with dynamic fixation as compared with static fixation with permanent screws. However, the lack of patients or personnel blinding, treatment heterogeneity, small samples, and short follow-up limit the overall quality of this evidence.